Biosynthesis of Iron Oxide Nanoparticles Using Escherichia coli - Hassan, Dunia Falah; Mahmood, Mahmood Basil (Iraqi Journal of Science, 2019)
This study proposed to synthesize iron oxide by biological method nanoparticles. The E.coli is used to reduce Ferric chloride salt into iron particles. The formation of iron oxide nanoparticle was initially monitored by visual observation and then characterized with the help of various characterization techniques such as Uv-vis spectroscopy, (AFM) and (FTIR) analysis, which revealed that the biosynthesized iron oxide nanoparticles were spherical within size 27.7 nm. Optimization of iron oxide nanoparticle biosynthesis by E.coli was performed for parameters (temperature and pH) and the results revealed that temperature 37Â°C and pH 5 were the optimum conditions for iron oxide nanoparticales biosynthesis by E.coli.